THE STUDY OF THE EFFECT OF RADIATION AND CHEMOTHERAPY ON THE FUNCTION OF THE HEART - Zavqiddin M. Kenjaev; Lola Dj. Sultanova (Central Asian Journal of Medicine, 2023)
The effect of chemoradiotherapy (CLT) on the cardiovascular system has been known since the 70s [4]. The dose-dependent cardiotoxicity of anthracycline antibiotic metabolites has been most well studied [6], which usually manifests itself already during treatment or in the first months and years after its completion. The most common of the early clinically significant cardiac complications of radiation therapy is effusion pericarditis. Lesions of the coronary arteries, valves, pericardial constriction and chronic heart failure (CHF), caused by progressive sclerotic changes in all structures of the heart, make their debut much later [3].